The Role of US institutions in developing effective international linkages for animal research and training in Latin America - Maner, JH (1980)
US Institutions and scientists have an important role to play in increasing world food production. At no time in history has such a tremendous concentration of scientific capability been so underutilized to remove the barriers that limit world food production that is so important to feed the millions of people who live in abject poverty and are plagued by hunger or malnutrition. The role of US institutions in developing effective international linkages for animal research and training to increase livestock production and income in Latin America is multiple and varied. Personnel from these institutions must include teachers, planners, developers, researchers, evaluators, politicians and diplomats if sound international collaborative efforts are to be developed and maintained. Our most capable scientists must commit their time and knowledge to the development of cooperative research programs which will provide solutions to the problems that limit animal production.